2023
DOI: 10.1002/ange.202214042
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Structure Transition and Peroxidase Mimic Activity of Copper Sites over Atomically Dispersed Copper‐Doped Carbonized Polymer Dots

Abstract: The lack of systematic structural resolution makes it difficult to build specific transition-metal-atom-doped carbonized polymer dots (TMA-doped CPDs). Herein, the structure-activity relationship between Cu atoms and CPDs was evaluated by studying the peroxidase-like properties of GluÀ CuÀ CPDs prepared by using copper glutamate (Glu) with a CuÀ N 2 O 2 initial structure. The results showed that the Cu atoms bound to GluÀ CuÀ CPDs in the form of CuÀ N 2 C 2 , indicating that CuÀ O bonds changed into CuÀ C bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Similarly, Chl‐Cu also possesses a Cu porphyrin structure. Our previous research confirmed the successful preparation of Cu‐CDs using Chl‐Cu as the carbon source [19] …”
Section: Selection Of Suitable Ligands For Preparation Of Tmas‐doped Cdssupporting
confidence: 76%
See 3 more Smart Citations
“…Similarly, Chl‐Cu also possesses a Cu porphyrin structure. Our previous research confirmed the successful preparation of Cu‐CDs using Chl‐Cu as the carbon source [19] …”
Section: Selection Of Suitable Ligands For Preparation Of Tmas‐doped Cdssupporting
confidence: 76%
“…Our previous research confirmed the successful preparation of Cu-CDs using Chl-Cu as the carbon source. [19]…”
Section: Selection Of Suitable Ligands For Preparation Of Tmas-doped Cdsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 For instance, Cu-N x O y -C with different nitrogen coordination numbers has been reported recently to unveil the influence of LCE on H 2 O 2 detection. 24 Therefore, SACs can be regarded as among the most promising nanozymes for single-molecule detections.…”
Section: Introductionmentioning
confidence: 99%